If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (K + -1p)(r + -1j) = 0 Reorder the terms: (K + -1p)(-1j + r) = 0 Multiply (K + -1p) * (-1j + r) (K(-1j + r) + -1p * (-1j + r)) = 0 ((-1j * K + r * K) + -1p * (-1j + r)) = 0 ((-1jK + rK) + -1p * (-1j + r)) = 0 (-1jK + rK + (-1j * -1p + r * -1p)) = 0 (-1jK + rK + (1jp + -1pr)) = 0 Reorder the terms: (-1jK + 1jp + -1pr + rK) = 0 (-1jK + 1jp + -1pr + rK) = 0 Solving -1jK + 1jp + -1pr + rK = 0 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add 'pr' to each side of the equation. -1jK + 1jp + -1pr + pr + rK = 0 + pr Combine like terms: -1pr + pr = 0 -1jK + 1jp + 0 + rK = 0 + pr -1jK + 1jp + rK = 0 + pr Remove the zero: -1jK + 1jp + rK = pr Add '-1rK' to each side of the equation. -1jK + 1jp + rK + -1rK = pr + -1rK Combine like terms: rK + -1rK = 0 -1jK + 1jp + 0 = pr + -1rK -1jK + 1jp = pr + -1rK Reorder the terms: -1jK + 1jp + -1pr + rK = pr + -1pr + -1rK + rK Combine like terms: pr + -1pr = 0 -1jK + 1jp + -1pr + rK = 0 + -1rK + rK -1jK + 1jp + -1pr + rK = -1rK + rK Combine like terms: -1rK + rK = 0 -1jK + 1jp + -1pr + rK = 0 The solution to this equation could not be determined.
| 3x^2-6x=x^2+x | | z+4=-4 | | m-8=-5 | | z+6=-6 | | z-7=3 | | z-7=0 | | 12+y=0 | | h/40=5 | | y-1.2=-1.3 | | 4x-3=x-15 | | a-5=66 | | x^2-6x+1=2-6x | | 5x-6=1-6x | | 7x-6=1-5x | | 6x^2+20x+12=0 | | x^2-5x+4=19-3x | | 4x+8-x+3=2x+23 | | y^2+3y+yx+3x=0 | | 10x-37=-87 | | x=8-3x | | (x-8)=4 | | (X*0.1)+X=100 | | (100*0.1)+100=X | | X*0.1=100 | | 6x+11=2x-1 | | (-3)(3+2x)+4x^2+1(1-x)=-11 | | 18x-x^2=71 | | 3x-15y=0 | | 2a+11=15 | | 36*(25+48)-16*22= | | 2x+36=6x+3 | | 7+5x=42 |